White epidermal nevus: a new early cutaneous sign of tuberous sclerosis complex. Case report and literature review. - Milano, A. (European Journal of Pediatric Dermatology, 2023)
White epidermal nevus is a condition described only in tuberous sclerosis complex. It has a different appearance and clinical course from other epidermal nevi and is precocious, sometimes appearing before the hypopigmented macules. When present, it could confirm early suspicion of tuberous sclerosis in sporadic cases in which genetic analysis does not reveal a pathogenic variant of TSC1 or TSC2. A clinical case followed for 14 years was presented and a review of the cases previously described in the literature was performed.